2021
DOI: 10.3390/biom11081114
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Recombinant hSP-D Binds and Inhibits SARS-CoV-2

Abstract: SARS-CoV-2 infection of host cells is driven by binding of the SARS-CoV-2 spike-(S)-protein to lung type II pneumocytes, followed by virus replication. Surfactant protein SP-D, member of the front-line immune defense of the lungs, binds glycosylated structures on invading pathogens such as viruses to induce their clearance from the lungs. The objective of this study is to measure the pulmonary SP-D levels in COVID-19 patients and demonstrate the activity of SP-D against SARS-CoV-2, opening the possibility of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…This causes the number of SP-Ds that leak into the systemic circulation is not much because the number of SP-Ds in the lungs from the beginning has decreased. This is supported by a study conducted by Arroyo, who found that COVID-19 patients exhibited decreased pulmonary SP-D serum levels (median = 68.9 ng/mL) compared to SP-D serum levels reported in the literature for healthy subjects, which ranged from 900-1300 ng/mL (Arroyo et al, 2021). This suggests that initial administration of natural surfactants should also improve lung function in adult patients with severe ARDS.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972supporting
confidence: 62%
“…This causes the number of SP-Ds that leak into the systemic circulation is not much because the number of SP-Ds in the lungs from the beginning has decreased. This is supported by a study conducted by Arroyo, who found that COVID-19 patients exhibited decreased pulmonary SP-D serum levels (median = 68.9 ng/mL) compared to SP-D serum levels reported in the literature for healthy subjects, which ranged from 900-1300 ng/mL (Arroyo et al, 2021). This suggests that initial administration of natural surfactants should also improve lung function in adult patients with severe ARDS.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972supporting
confidence: 62%
“…Arroyo et al studied 12 patients > 18 years old who had respiratory failure requiring intubation and mechanical ventilation secondary to COVID-19 ( 5 ). SARS-CoV-2 infection was confirmed with PCR testing.…”
Section: Human Surfactant Protein D Is Depleted In Patients With Covi...mentioning
confidence: 99%
“…Arroyo et al also demonstrated that a full-length recombinant human SP-D bound the Spike protein (S-protein) of the SARS-CoV-2 virus in a calcium-dependent manner involving the carbohydrate recognition domain ( 5 ). This process also showed that protein cross bridges formed when binding the S-protein in the presence of another molecule (maltose-coated beads) suggesting the ability of SP-D to aggregate the virus and potentially facilitate viral clearance.…”
Section: Human Surfactant Protein D Is Depleted In Patients With Covi...mentioning
confidence: 99%
See 2 more Smart Citations